Pojęcie i cechy charakterystyczne odpowiedzialności dyscyplinarnej w prawie polskim: [Term and characteristics of disciplinary liability in polish law] (Studia Prawnicze / The Legal Studies, 2015)
Po trwającym ponad 40 lat okresie, kiedy odpowiedzialność dyscyplinarna znajdowała się właściwie poza zakresem zainteresowania doktryny, w ostatnich kilkunastu latach pojawiły się liczne publikacje, odnoszące się jednak zazwyczaj do poszczególnych grup zawodowych lub wybranych instytucji prawa dyscyplinarnego. Niewątpliwie ten wzrost zainteresowania jest nie tylko wynikiem dostrzeżenia, że taki rodzaj odpowiedzialności dotyczy coraz większej liczby wspólnot, ale przede wszystkim zwiększonego „wyczulenia” na kwestię represyjności prawa. Problemem, jaki wiąże się z odpowiedzialnością dyscyplinarną jest bowiem nie tylko to, że jest to odpowiedzialność często bardzo surowa, ale przede wszystkim to, że stopień tej surowości nie zawsze koresponduje ze sposobem unormowania w sposób zapewniający przestrzeganie praw osoby jej poddanej.Porównanie poszczególnych regulacji dyscyplinarnych bardzo wyraźnie wskazuje, że są one niespójne, a w niektórych przypadkach ustawodawca ograniczył się wręcz jedynie do zarysowania pewnego schematu egzekwowania tej odpowiedzialności, uszczegółowienie go pozostawiając przepisom rangi podstawowej. However for last 40 years disciplinary liability was generally out of scope of doctrine, recently it is noted constant increase of interest of that part of law. There are many reasons for that, including involving new professional groups and respective strictness and inconsistence of disciplinary provisions. The latter is aggravated by heterogenicity in various corporations and governing by substatutory regulations. Unfortunatelly, an unification of criminal law, being applied mutatis mutandi, is only partial remedy.In that elaboration author analyzed regulations between various corporations to extract basic and common rules and to denominate differences. The complexity augments fact that not only acts have binding effect, but also delegated regulations. That creates sophisticated network of law and professional knowledge, with additional problem of overlapping lex generalis and lex specialis in uncommon proportion. Above mentioned differences concern not only substantive law but also, if not even wider, procedural one. Interestingly, what author depicts, there is even not identical wording used in description of analogical names or definitions.Disciplinary liability, as cumulative to the criminal one, tends to protecting rights of accused person, as generally rule ne bis in idem is not in force. It concerns basic rights, like dignity and equality under the law.It is necessary strict cooperation and open discussion between professionals and legislator, as proper disciplinary liability rules need both protect society and allow to realize freely duties of practitioners.